(untitled) - Doyle, Jon (New York, 2013)
Create Success provides students and instructors with the tools needed to foster these relationships. With agile social learning, instructors can immediately facilitate an active and engaged classroom environment and help students create connections with each other and the school community.
Keywords: Education, Higher,Giáo dục Đại học; Curricula,Chương trình học; United States,Hoa Kỳ